Histochemical Changes Liver and Kidney of Mice Exposed to Mercury and Recovery with Nanogold - Titik Taufikurohmah; I Gusti Made Sanjaya; Afaf Baktir; Achmad Syahrani (Universitas Jenderal Soedirman, 2016)
The background of this research is the circulation cosmetic with mercury that occur today in society. The problem of the research is that occur histochemical’s damage liver and kidney after exposure to mercury, and is that nanogold can recovery that damage. The pre-clinical study needed 24 mice (Mus muscullus) were divided into 6 groups, the control is A group, B group was exposed to mercury, Groups C, D, E and F after being exposed to mercury, than recovery by nanogold with concentration each of 5, 10, 15 and 20 ppm. Exposure was performed 1 week and 4 weeks of recovery. Necropsy of mice doing after treatment, liver and kidneys are processed into preparations by blocking with paraffin embedding method. Histochemical staining of liver and kidney tissue with Hematoxylin eosin (HE) to determine changes of cell constituent and staining Van Geyson to determine the structure of collagen constituent. Statistics Manova showed different results between treatment groups. Tissue damage, lysis cell and destruction of collagen can be observed from histochemical techniques for mercury-exposed group compared to the control group. Tissue and collagen recovery process can be observed from group C, D, E and F. The conclusion that the effects of mercury one week exposed through skin give effect to collagen tissue damage at liver and kidneys of mice. 20 ppm of Nanogold can recovery damaged cells and collagen tissue from the liver and kidneys of mice after four weeks of recovery.